Transnationalism and migrant entrepreneurship: a case study of self-employed foreigners in Hangzhou, China. (4th July 2022) - Chen, Zhenxiang; Fan, Xiaoguang
Abstract: International migrant entrepreneurship in China has expanded and grown. Yet, studies on this phenomenon in China have been limited. We aim to contribute to this literature by exploring international migrant entrepreneurship for various categories of international migrants in a single setting and suggesting a more comprehensive picture of migrant entrepreneurship in China. We rely on the transnationalism framework and conduct various regression analyses using our unique dataset—Survey of Foreigner Residents in China (SFRC) from 2018-2019 to study both factors in China and factors from migrants' home country, as well as the interactions between these two types of factors, in determining migrants' likelihood of being an entrepreneur. Our results suggest that social networks and language skills in China, the ownership of the assets in migrants' home country, and the economy and culture of their home country can significantly shape migrants' likelihood to become an entrepreneur. These findings show the major role of factors from migrants' home country, highlighting the importance of using the transnationalism framework to study migrant entrepreneurship. We also find evidence of only a few interaction effects between factors in China and factors from migrants' home country, suggesting that they are weakly dependent on each other in influencing migrant entrepreneurship in China.